2020
DOI: 10.1016/j.ijid.2019.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Use of GeneXpert MTB/RIF on a single pooled sputum specimen to exclude pulmonary tuberculosis among hospital inpatients placed in respiratory isolation

Abstract: Background: Patients with suspected pulmonary tuberculosis (PTB) are usually placed in respiratory isolation awaiting three sputum smear microscopy results for acid-fast bacilli (3AFB). GeneXpert MTB/ RIF (Xpert) on a pooled sample from two sputa may allow for more rapid de-isolation. Objectives: To compare the sensitivity and negative predictive value (NPV) of Xpert performed on a single pooled sputum sample ('pooled Xpert') to 3AFB, in order to exclude PTB in patients placed in respiratory isolation. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…In addition to lung specimens, the ability of GeneXpert MTB/RIF to detect M. tuberculosis in gastric fluid (Tan et al, 2020;van Brusselen et al, 2020), urine (Chen et al, 2020), cerebrospinal fluid (Patel et al, 2020), and biopsy tissue samples (Solanki et al, 2019) has also been verified in previous reports. It was also reported in a previous study that the sensitivity of a single GeneXpert MTB/RIF experiment to diagnose tuberculosis was 88.9% (95% CI 57-99%), which was higher than that of three acid-fast staining experiments (66.7%; 95% CI 35-88%) (Yeong et al, 2020). In this study, the sensitivity of GeneXpert MTB/RIF to diagnose PTB was 89.00%, and even in patients with negative acid-fast staining, the PTB positive rate was 72.41%.…”
Section: Discussionmentioning
confidence: 52%
“…In addition to lung specimens, the ability of GeneXpert MTB/RIF to detect M. tuberculosis in gastric fluid (Tan et al, 2020;van Brusselen et al, 2020), urine (Chen et al, 2020), cerebrospinal fluid (Patel et al, 2020), and biopsy tissue samples (Solanki et al, 2019) has also been verified in previous reports. It was also reported in a previous study that the sensitivity of a single GeneXpert MTB/RIF experiment to diagnose tuberculosis was 88.9% (95% CI 57-99%), which was higher than that of three acid-fast staining experiments (66.7%; 95% CI 35-88%) (Yeong et al, 2020). In this study, the sensitivity of GeneXpert MTB/RIF to diagnose PTB was 89.00%, and even in patients with negative acid-fast staining, the PTB positive rate was 72.41%.…”
Section: Discussionmentioning
confidence: 52%
“…20 Meanwhile, research in China shows that high BMI and obesity are associated with the risk of TB infection, possibly because the excess cell adiposity weakens the immune system. 30 The majority of patients showed that vital signs were outside the normal limits, and the results of the study showed that most of the patients had abnormal temperatures, which was in 33.3% of patients. Another study states Indonesian Journal of Tropical and Infectious Disease, Vol.…”
Section: Discussionmentioning
confidence: 82%
“…GeneXpert is recommended by the World Health Organization in the pulmonary and extra-pulmonary tuberculosis diagnosis in both immunocompetent and immunocompromised patients [8,9]. It is a rapid molecular test with high performance (sensitivity and specificity) [10].…”
Section: Discussionmentioning
confidence: 99%
“…It is a rapid molecular test with high performance (sensitivity and specificity) [10]. Multiple gen-eXpert testing on bronchoalveolar lavage fluid can improve the test sensitivity [9].…”
Section: Discussionmentioning
confidence: 99%